Effects of static stretching and walking during inter-set intervals of resistance training on muscle fatigue of the quadriceps - Takeuchi, Kosuke; Inoue, Hiroaki; Fujiwara, Motoka; Shimizu, Taiki; Nagai, Chiharu; Mizuno, Kosei; Nakamura, Masatoshi (Frontiers in Sports and Active Living, 2025)
IntroductionInter-set rest intervals are essential to reduce muscle fatigue and increase the total amount of volume of resistance training. Static stretching and walking may increase muscle blood flow and promote recovery during inter-set rest intervals. Therefore, the purpose of this study was to investigate the effects of 20 seconds of static stretching and walking during inter-set rest intervals of leg extension exercises on the number of repetitions to exhaustion, total amount of volume, and flexibility of the quadriceps (joint range of motion and muscle hardness) in untrained healthy males.MethodsFourteen healthy, untrained men performed three different interventions (passive rest, static stretching, and walking) during inter-set rest intervals of a leg extension exercise with a 70% load of maximum muscle strength, in random order. The range of motion and muscle hardness of the quadriceps were measured before and immediately after all interventions using a goniometer and a portable muscle hardness meter. The number of repetitions to exhaustion and total amount of volume load (load × repetitions) of the leg extension exercise were assessed. Repeated two-way ANOVA and a Friedman test were used to analyze the variables.ResultsRange of motion and muscle hardness were increased after all interventions (both p < 0.05). There was no significant difference in the number of repetitions to exhaustion (p = 0.651) or total amount of volume load (p = 0.206) between interventions.DiscussionThese results indicated that static stretching and walking during inter-set rest intervals did not influence the change in flexibility and muscle fatigue of the leg extension exercise.